Composite valved apico-aortic conduits for left ventricular outflow obstruction. - Cooley, Denton A. (1980)
Problems related to the left ventricular outflow tract are not always amenable to conventional surgical methods, and in some cases may be solved with the creation of a double outlet left ventricle, using a composite rigid pyrolite left ventricular apex outlet prosthesis and a fabric valve-containing conduit. The primary indication for apico-aortic conduits is severe left ventricular outlet obstruction that is not correctable by conventional surgical techniques. Failure to relieve ventricular hypertension causes persistent physiologic derangements that include increased left ventricular work and oxygen consumption. decreased cardiac output, and compromise of coronary perfusion. Our clinical experience in excess of 18 months with valved apicoaortic conduits for primary or recurrent left ventricular outflow tract obstructions has been promising and is described in this report.